Pengaruh Model Pembelajaran Guided Discovery Learning Terhadap Literasi Kimia Peserta Didik Pada Materi Larutan Penyangga - Darwis, Darsef; Permatasari, Nur Azmi; Nurjayadi, Muktiningsih (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
The purpose of this research was to know the effect of guided discovery learning models on students' chemical literacy in the buffer solution material. This research was conducted at SMAN 53 Jakarta in the even semester of the 2018/2019 academic year. The research method was quasi experiment. The sample in this study was selected through purposive random sampling. The study sample consist of two classes, XI MIPA 4 as the control class and Class XI MIPA 3 as the experimental class. The control class gets learning with discussion methods and the experimental class gets learning with guided discovery learning models. Based on the results of data analysis, the value of tcount is 5.568 and the value of ttable is 2.001 with df = 59 and the significance level is α = 0.05. The results of this study indicate that the tcount is greater than ttable (5.568> 2.001), it can be concluded that there is a positive influence on the application of guided discovery learning learning models to students' chemical literacy in the buffer solution material. Keywords Guided Discovery Learning Model, Chemical Literacy, Buffer Solution